FORMAÇÃO E CUMPRIMENTO DE CONTRATOS ELETRÔNICOS NO SISTEMA DE COMÉRCIO INTELIGENTE - ICS - Oliveira, Nathália Ribeiro Schalcher de (2004)
This work is part of the ICS Project, which has been developed in LSI at UFMA under the coordinator Sofiane Labidi s assistance. The main objective is to develop an intelligent environment to deal with the last two phases of the ICS lifecycle: the Formation and Fulfillment of Contracts. The ICS architecture and environment are presented as well as its development aspects. An implemented system that uses intelligent agent has the possibility to automatize the mechanism of closed deal contract among ICS users, as well as the monitoring of its assumed obligations. We propose the use of patterns and Semantic Web tools to deal with the information management included in the contracts. Related to the monitoring we propose a model that makes use of the Temporal Workflow and of active rules based on the ECAA s paradigm of Active Database System.